Risiko dalam Implementasi Free On Board (FOB) Berdasarkan Incoterms 2010 pada Penyelenggaraan Pengangkutan Laut - Zefanya, Anastasia; Trisnamansyah, Purnama; Maulana, Mursal (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
Incoterms 2010, issued by the International Chamber of Commerce and effective January 1,2011, is a set of rules for the delivery of products between sellers and buyers that are routinelyincluded in international sales contracts. Incoterms 2010 provides harmonized rules ofinterpretation for eleven general trading terms. From these eleven common terms, a trader mustselect the Incoterms that are most appropriate for the specific transaction he wishes to undertake.If used correctly, Incoterms 2010 is an effective risk management tool. However, old tradingpractices create tensions with modern transportation practices and Incoterms 2010, potentiallyincreasing risks for traders. When using Incoterms, Free On Board (FOB) terms are the mostfrequently used in transportation methods. This article intends to examine what risks occur in usingthe term FOB, especially in sea transportation. The type of research used in this paper is normativelegal research (normative analysis) using library materials as a source of research data.Furthermore, this article intends to provide support to traders to learn more about FOB so that theycan propose criteria that might be applied to choose the most appropriate Incoterm. Therefore, thiswill be the basis of how the mode of transport influences and sometimes even determines choices fora certain period of time.